Given the system of equations:
[tex]\begin{cases}y={5x-3} \\ y={-6x+8}\end{cases}[/tex]
We solve it using the substitution method, then:
[tex]5x-3=-6x+8[/tex]
We add 6x on both sides of the equation:
[tex]\begin{gathered} 5x-3+6x=-6x+8+6x \\ 11x-3=8 \end{gathered}[/tex]
Now, we add 3 on both sides:
[tex]\begin{gathered} 11x-3+3=8+3 \\ 11x=11 \end{gathered}[/tex]
Finally, we divide by 11 on both sides:
[tex]\begin{gathered} \frac{11x}{11}=\frac{11}{11} \\ \\ \therefore x=1 \end{gathered}[/tex]
And the solution is:
[tex]\begin{gathered} x=1 \\ y=2 \end{gathered}[/tex]